Onset, course, and outcome of schizophrenia. - Rakfeldt, Jaak; McGlashan, Thomas (Current Opinions in Psychiatry, 1996)
The studies reviewed here reflect many important aspects of the onset, course, and outcome of schizophrenia; that is, premorbid factors, childhood and late-life onset, the positive-negative syndrome dichotomy, co-occurring substance abuse, outcome research, and theoretical issues. Unsurprisingly, heterogeneity of course and outcome emerges as a major theme., (C) Lippincott-Raven Publishers.
Keywords: depression; dept.swk; disease course; human; onset age; schizophrenia; short survey; substance abuse

Working memory, attention, and communication disturbances in schizophrenia. - Docherty, Nancy M; Hawkins, Keith A; Hoffman, Ralph E; Quinlan, Donald M; Rakfeldt, Jaak; Sledge, William H (Journal of Abnormal Psychology, 1996)
The authors hypothesized that schizophrenic communication disturbances reflect specific cognitive deficits in the areas of working memory and attention. They examined the cognitive correlates of communication disturbances, as measured by linguistic reference performance, in schizophrenic (n = 48), bipolar (n = 24), and nonpsychiatric control (n = 23) individuals. Reference performance ratings in the schizophrenic patients were associated with scores on tests of working memory and attention and were not related to performance on concept formation or verbal fluency tests. In contrast, in the bipolar and nonpsychiatric individuals, reference performance was associated with concept formation and verbal fluency test scores but was not related to performance on tests of working memory. Implications with respect to the processes underlying schizophrenic communication disturbances are discussed.
Keywords: adult; article; attention; bipolar depression; cognitive defect; controlled study; dept.swk; female; human; interpersonal communication; major clinical study; male; memory; rating scale; schizophrenia; task performance; verbal communication

Persistence by 2-Year college graduates to 4-Year colleges and universities. - Dworkin, Stephen L (Community College Journal of Research and Practice, 1996)
Most community college graduates do not continue on for study in 4-year colleges and universities. Fewer than 20% do so within the first few years after receiving their associate's degrees. Concerns have been expressed about the extent to which older students (e.g., students who received their degrees at age 25 and above) persist (go on) to 4-year colleges and universities and about the correlates of persistence for this group. The purpose of this study was to examine the relationships between a selected number of academic, social, and personal variables in the context of predicting persistence to a 4-year public university among older graduates of a New England state’s public 2-year institutions. Data were collected in 1988 and 1989 from a random sample of 3,762 older associate's degree students from the 12 community colleges in Connecticut. These data were then subjected to a two-group, single-function discriminant function analysis to determine the predictive power of the dependent measures used in the study. The results indicated that the higher the perceptions of social and institutional support in community colleges and the higher the age of the graduates, the more apt they were to persist to a 4-year institution. Further analysis, however, revealed that the average persister was 38 years old, whereas the average attritor was 34 years old, suggesting the need for further research among 2-year college populations among the over-30 age group as well as replication of the study in states with both similar and dissimilar demographic shifts in college populations. © 1996 Taylor and Francis Group, LLC.
Keywords: dept.swk